Antimicrobial and antiproliferative activities of stingless bee Melipona scutellaris geopropolis - da Cunha Marcos Guilherme; Franchin Marcelo; Galvão LíviaCâmaradeCarvalho; de Ruiz AnaLúciaTascaGóis; de Carvalho João Ernesto; Ikegaki Masarahu; de Alencar Severino Matias; Koo Hyun; Rosalen Pedro Luiz (BMC, 2013)
Abstract Background Geopropolis is a type of propolis containing resin, wax, and soil, collected by threatened stingless bee species native to tropical countries and used in folk medicine. However, studies concerning the biological activity and chemical composition of geopropolis are scarce. In this study, we evaluated the antimicrobial and antiproliferative activity of the ethanolic extract of geopropolis (EEGP) collected by Melipona scutellaris and its bioactive fraction against important clinical microorganisms as well as their in vitro cytotoxicity and chemical profile. Methods The antimicrobial activity of EEGP and fractions was examined by determining their minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) against six bacteria strains as well as their ability to inhibit Streptococcus mutans biofilm adherence. Total growth inhibition (TGI) was chosen to assay the antiproliferative activity of EEGP and its bioactive fraction against normal and cancer cell lines. The chemical composition of M. scutellaris geopropolis was identified by reversed-phase high-performance liquid chromatography and gas chromatography-mass spectrometry. Results EEGP significantly inhibited the growth of Staphylococcus aureus strains and S. mutans at low concentrations, and its hexane fraction (HF) presented the highest antibacterial activity. Also, both EEGP and HF inhibited S. mutans biofilm adherence (p < 0.05) and showed selectivity against human cancer cell lines, although only HF demonstrated selectivity at low concentrations. The chemical analyses performed suggest the absence of flavonoids and the presence of benzophenones as geopropolis major compounds. Conclusions The empirical use of this unique type of geopropolis by folk medicine practitioners was confirmed in the present study, since it showed antimicrobial and antiproliferative potential against the cancer cell lines studied. It is possible that the major compounds found in this type of geopropolis are responsible for its properties.